2017
DOI: 10.1017/s0954422416000287
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic consequences of obesity and insulin resistance in polycystic ovary syndrome: diagnostic and methodological challenges

Abstract: Women with polycystic ovary syndrome (PCOS) have a considerable risk of metabolic dysfunction. This review aims to present contemporary knowledge on obesity, insulin resistance and PCOS with emphasis on the diagnostic and methodological challenges encountered in research and clinical practice. Variable diagnostic criteria for PCOS and associated phenotypes are frequently published. Targeted searches were conducted to identify all available data concerning the association of obesity and insulin resistance with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
89
0
16

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(107 citation statements)
references
References 125 publications
2
89
0
16
Order By: Relevance
“…Both excess extracellular glucose and insulin suppressed the levels of GLUT4, SREBF1 and HMGA2 by upregulating miR-33b-5p, whereas GLUT4, SREBF1 and HMGA2 levels became elevated when miR-33b-5p was inhibited, indicating the powerful effects that glucose and insulin exert in the regulation of GLUT4, SREBF1 and HMGA2 by miR-33b-5p. Insulin resistance is a main feature of PCOS, and can adversely affect a woman's health (8,44,45). GLUT4 is strongly linked to the development of insulin resistance in type 2 diabetes or PCOS (46,47).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both excess extracellular glucose and insulin suppressed the levels of GLUT4, SREBF1 and HMGA2 by upregulating miR-33b-5p, whereas GLUT4, SREBF1 and HMGA2 levels became elevated when miR-33b-5p was inhibited, indicating the powerful effects that glucose and insulin exert in the regulation of GLUT4, SREBF1 and HMGA2 by miR-33b-5p. Insulin resistance is a main feature of PCOS, and can adversely affect a woman's health (8,44,45). GLUT4 is strongly linked to the development of insulin resistance in type 2 diabetes or PCOS (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…Presently, the pathogenesis of PCOS is not fully understood, and requires further investigation. More than 50% of PCOS patients are insulin resistant (2,8), which can partly explain their increased risk for diabetes and cardiovascular disease. Furthermore, insulin resistance can also be the cause for hyperlipidemia and hyperinsulinemia in PCOS patients.…”
Section: Introductionmentioning
confidence: 99%
“…In keeping with the local guidelines, all mothers were provided standard diet during pregnancy as recommended by the Iranian Ministry of Health guidelines. According to 2003 Rotterdam criteria [4], the diagnostic traits of PCOS are the presence of two or more significant symptoms of the syndrome and patients that met two of three symptoms were chosen. PCOS diagnosis was done by the medical practitioners affiliated to Royan Institute.…”
Section: Subjects and Adipose Tissue Biopsiesmentioning
confidence: 99%
“…Therefore, more investigations on effective several factors including AT roles in PCOS are necessary. [4] It has been suggested that AT may involve in PCOS and androgen excess was closely related to the lipid metabolism disorder. Actually, AT is not only recognized as a fat storage organ but is also regarded as an organ with important endocrine and metabolic functions [5] and subcutaneous fat biopsies can be used as an integrated long-term indicators of FA metabolism [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…PCOS share many features with the metabolic syndrome so that the majority of PCOS women (44-85%) (10,51) have insulin resistance (IR) and the compensatory hyperinsulinemia regardless of BMI [2][3][4].…”
Section: Introductionmentioning
confidence: 99%